2010
DOI: 10.1093/bja/aeq089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nociceptin/orphanin FQ and μ-opioid receptor mRNA in the human right atrium

Abstract: The human right atrium of patients with coronary artery disease and heart failure expresses mRNA encoding NOP and possibly low levels of MOP. This does not correlate with degree of cardiac dysfunction. In addition, the atrium does not express ppN/OFQ mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Most of studies failed to detect this OR subtype in the heart (Ventura et al, 1989;Zimlichman et al, 1996;Weil et al, 2006;Bolte et al, 2009;Karlsson et al, 2012). However, Head et al (2005) found the μ-OR on the sarcolemma of cardiac myocytes and its transcript was detected in the human atrium (McDonald et al, 2010). Further investigation is needed to resolve this issue.…”
Section: Discussionmentioning
confidence: 98%
“…Most of studies failed to detect this OR subtype in the heart (Ventura et al, 1989;Zimlichman et al, 1996;Weil et al, 2006;Bolte et al, 2009;Karlsson et al, 2012). However, Head et al (2005) found the μ-OR on the sarcolemma of cardiac myocytes and its transcript was detected in the human atrium (McDonald et al, 2010). Further investigation is needed to resolve this issue.…”
Section: Discussionmentioning
confidence: 98%
“…5). NOP receptors are known to be present in human heart (20) and spleen, an organ rich in immune cells (21). Functional studies in exocrine pancreas of guinea pig indicated the presence of NOP receptors in pancreatic lobules (22).…”
Section: Discussionmentioning
confidence: 99%
“…To date, anatomic evidence for the different OR subtypes in the human heart has been scarce. Most investigators have confirmed the presence of DOR mRNA and protein, but there is still conflicting evidence for MOR and KOR [18][19][20]. Moreover, immunohistochemical studies of their anatomic distribution are lacking.…”
Section: Introductionmentioning
confidence: 99%